Lamb Wave Based Ultrasonic Technique for AA2024 Fatigue Evaluation; Key Engineering Materials; Vol. 685 : High Technology: Research and Applications 2015 (HTRA 2015) - Burkov M. V. Mikhail Vladimirovich; Eremin A. V. Alexandr Vyacheslavovich; Byakov A. V. Anton Viktorovich; Shah R. T.; Lyubutin P. S. Pavel Stepanovich; Panin S. V. Sergey Viktorovich (Mechanical Engineering Technology, 2016)
Title screen